Documentary research in the social sciences - Tight, Malcolm (Sage, 2019)
"From diaries and letters to surveys and interview transcripts, documents are a cornerstone of social science research. This book guides you through the documentary research process, from choosing the best research design, through data collection and analysis, to publishing and sharing research findings."--Publisher's website.